The relationship between varicocele and body mass index: a systematic review - Mitra Savabi Esfahani; Marzieh Ghasemi Gujani; Soheila Mohamadirizi (Mashhad University of Medical Sciences, 2021)
Introduction: Varicocele is one of the most important causes of male infertility that is affected by various factors including anthropometric indices. Body mass index can change the prevalence of varicocele in men and although there are many studies on the relationship between BMI and the prevalence of varicocele, but no study has reviewed these results, so this review study was performed with aim to evaluate the relationship between body mass index and varicocele in various studies. Methods: In this review study, international databases of Web of Science, Scopous, Proquest and Pubmed and Iranian databases such as Irondoc, Magiran, and SID were searched for findings the studies published between 2000 and 2020 using the related keywords. The full text of selected articles was reviewed by two browsers. Results: A total of 10 studies were reviewed. These studies examined the body mass index of men and examined the prevalence of varicocele in these individuals. Most studies have shown that obese men and people who reported a higher body mass index had a lower prevalence of varicocele and a high body mass index could be a protective and preventive factor in men. Conclusion: According to the results of this study, body mass index is associated with the incidence of varicocele and people with low body mass index have higher incidence of varicocele than people with normal body mass index.